NUTRITIONAL STATUS OF AGED TRIBAL PEOPLE: A STUDY OF BIRHOR COMMUNITY IN PURULIYA DISTRICT, WEST BENGAL (International Journal of Food and Nutritional Sciences, 2022)
TheNutritionalStatusandsocio-economicprofileoftribalpeopleisanessentialissueinIndiadue to their marginalization from the mainstream population concerning various facilities.Under-nutritionisoneofthemain factorscontributingtomorbidityanddeaththeDevelopingNations. India is home to more than half of the world's undernourished people. As determinedby Body Mass Index (BMI), Chronic Energy Deficit (CED) prevalence is a reliable predictorof the population's poor demographic, socio-economic, and environmental circumstances,particularly among adults in developing nations. In addition, 57% of stroke fatalities and 24%ofdeathsfromCoronaryHeartDisease(CHD)inIndiaaredirectlyattributabletohypertension.Consideringthestandardofsocio-economicandsocio-demographicvariables,itisundeniablethatthe tribesofIndiaarethe weakestsegmentsof the population.The term ‘Birhor’ is derived from the Mundari dialect, where ‘Bir’ means forest and ‘hor’stands for man of the jungle. Through the ages, Birhor folk have been living a nomadic life.Anthropologists have classified Birhor tribes as a proto-austroloid racial group and theirlanguage has been kept in Mundari group of languages. Loss of perpetual rights on forestresources,lackofemploymentopportunities,unfulfilledpromisesbypoliticiansandhankeringfor bread and butter, these people are leading a miserable life. In 1971, their population in theChotanagpur region was 3,598. In 1981, it touched 4,377. According to the Indian NationalTrust for the Welfare of Tribals (Intwot) survey their population now is (Census 2011) only5017.It is therefore, very crucial to investigate the socio-economic condition of the Birhore tribeconcerning their employment, way of life, income status, level of education, eating habits andstandardoflife.Thispaperisanefforttoanalysesthesocio-economiccircumstancesoftheagedmembersofBirhoretribeinthePuruliyadistrictbyassessingthenutritionalstatusandresearchonthe relationship between BMIand hypertension in the elderly tribalpopulation.